A Novel Variant in CWF19L1 Gene in a Family with Late-Onset Autosomal Recessive Cerebellar Ataxia 17. (1st February 2021) - Algahtani, Hussein; Shirah, Bader; Almatrafi, Samah; Al-Qahtani, Mohammad H.; Abdulkareem, Angham Abdulrahman; Naseer, Muhammad Imran
ABSTRACT: Introduction: Previously published studies demonstrated that mutations in CWF19L1 cause early-onset autosomal recessive cerebellar ataxia 17. In this article, we report a novel homozygous missense variant in CWF19L1 in two sisters who had late-onset cerebellar ataxia with epilepsy and describe their clinical and neuroradiological findings. Methods: We included two female patients with typical symptoms of cerebellar ataxia supported by the MRI findings. Whole exome sequencing (WES) data analysis was performed to identify the underlying genetic defect in the proband. Sanger sequencing was used to confirm the variant in other family members. Results: WES revealed a homozygous missense variant in CWF19-like protein 1; CWF19L1 gene c.395A>G; p.(Asp132Gly) (RefSeq NM_018294.4). This variant has not been described previously in the literature. Mutations in this gene are known to cause an autosomal recessive disorder, spinocerebellar ataxia, autosomal recessive 17 (OMIM #616127). Conclusion: In conclusion, we report a novel variant in CWF19L1 as a candidate causal variant in two sisters with autosomal recessive cerebellar ataxia. This is the first report coming from Arab countries. Additional reports in patients with a progressive course and adult-onset are needed, but this could be the first report of this disease diagnosed in adulthood since it is a disease of children and adolescents. In addition, our patients had epileptic seizures, which were not previously documented in patients with CWF19L1 mutations. We postulate that mutations in this gene have widespread functional and structural changes in multiple levels of the neuraxis rather than being a pure cerebellar disorder.